Prediction of Function Determining and Buried Residues Through Analysis of Saturation Mutagenesis Datasets - Bhasin, Munmun; Varadarajan, Raghavan (Frontiers in Molecular Biosciences, 2021)
Mutational scanning can be used to probe effects of large numbers of point mutations on protein function. Positions affected by mutation are primarily at either buried or at exposed residues directly involved in function. In the absence of prior structural information, it has not been easy to distinguish between these two categories of residues. We curated and analysed a set of twelve published deep mutational scanning datasets. The analysis revealed differential patterns of mutational sensitivity and substitution preferences at buried and exposed positions. Prediction of buried-sites solely from the mutational sensitivity data was facilitated by incorporating predicted sequence-based accessibility values. For active-site residues we observed mean sensitivity, specificity and accuracy of 66, 91 and 88% respectively. For buried residues the corresponding figures were 55, 88 and 82% while for exposed non active-site residues these were 93, 34 and 75% respectively. We also identified positions which did not follow these general trends and might require further experimental re-validation. This analysis highlights the ability of deep mutational scans to provide important structural and functional insights, even in the absence of three dimensional structures determined using conventional structure determination techniques.